The Effect of Crystal-Based Learning with Authentic Assessment on Science Competency of Students in First Secondary School - Wongwattana, Julaluck; Langka, Wilailak; Suwathanpornkul, Ittipaat (Academic MCU Buriram Journal, 2021)
The purposes of this research are as follows: (1) to compare the scientific competency of in First Secondary School students who received crystal-based learning with authentic assessment when controlling scientific identity. The research sample consisted of 24 in First Secondary School students of Kanoksinpittayakom School during the second semester of the 2020 academic year, which was obtained by Multi-stage Sampling. The research instruments consisted of a scientific identity assessment scale, crystal-based learning with authentic assessment management plan and tests of science competency. The statistics employed for data analysis were mean, standard deviation and One-Way Repeated Measures ANCOVA. The results of the research were as follows: scientific identity affecting science competency from all three repeated tests at a statistically significant level of .05. (F= 86.853, p =0.000) When comparing the scientific competency scores of the students, who learned with crystal-based learning with authentic assessment from all three repeated tests with scientific identity as a covariate variable. The results of comparing each pair were found that the Scientific Competency Mean Score, Unit 1 and Unit 2, had a statistically significant difference of .05 (p = 0.000).